Pneumonia Prevalence and Associated Risk Factors among under-Five Children in Goncha Siso Enesie District, Northwest Ethiopia - Bizualem Abebaw; Destaw Damtie (Hindawi Limited, 2022)
Background. Pneumonia is one of the leading causes of morbidity and mortality among under-five children in various localities of Ethiopia. This study was aimed to assess the prevalence of pneumonia and its associated factors among under-five children who were visiting Ginde Woyin health center, Goncha Siso Enesie District, Northwest Ethiopia. Methods. A health center-based cross-sectional study was conducted among 403 participants by a systematic random sampling technique. Data were collected using questionnaires and sputum diagnosis. Data were analyzed using Statistical Package for Social Science (SPSS) version 26.0. Binary and multivariable logistic regressions were used to analyze the risk variables, and P values < 0.05 were considered statistically significant. Results. The overall prevalence of pneumonia among under-five children was 24.3% (95% CI: 20.1, 28.3). The significant predictors for under-five pneumonia identified were the use of wood as a source of fuel for cooking (AOR = 2.769; P=0.049), starting complementary food before six months of age (AOR = 2.080; P = 0.033), and mixed breastfeeding conditions (AOR = 5.229; P=0.001). The highest under-five pneumonia was observed among children of age below one year (33.6%), rural dwellers (30.4%), family sizes above five (31.8%), children from families with a monthly income of less than 1000 Ethiopian Birr (<19.03 USD) (27.8%), whose mothers were students (61.5%), houses where cooking took place in the living room (37.8%), homes that lacked windows in the kitchens (28.4%), homes that lacked windows (41.5%), and mixed breastfeeders (44.1%). Conclusion. The prevalence of under-five pneumonia in the present study was relatively high. The findings in the present study will help policy makers and program officers to design pneumonia-preventive interventions.